The Effectiveness of Ted-Ed as Video Based Media Towards High School Students’ Listening Skill - Kadek Febriana Merdianti; Made Hery Santosa; Kadek Sintya Dewi (JELLT (Journal of English Language and Language Teaching), 2023)
Abstract: The use of technological tools to teach English skill, especially listening, has proved by previous study bring a positive effect towards students’ performance. Therefore, this study aimed to see the effectiveness of TED-Ed as video based media on students’ listening skill at SMAN 1 Singaraja, Bali. This research is an experimental study, in which applied quasi-experimental design with post-test only control-group design. The data were collected through post-test and later, the post-test result from both groups were compared and analyzed. The result showed that the mean score of experimental group was higher than the control group, 80,03 > 75,49. It indicates that the group taught with TED-Ed had better result than the other group who taught by using audio based media. Moreover, the sig. (2-tailed) value in the independent sample t-test was lower than 0,5, in which 0,003. It means that there was a significant effect towards the use of TED-Ed on student’s listening skill. Therefore, TED-Ed affects the students’ listening skill and makes the students perform better than the use of audio based media. Abstrak: Penggunaan teknologi dalam mengajar Bahasa Inggris, terutama dalam listening, telah dibuktikan oleh beberapa peneliti terdahulu dapat memberi dampak yang positif terhadap siswa. Oleh karena itu, penelitian ini bertujuan untuk melihat efek yang diberikan oleh TED-Ed sebagai media belajar berbasis video terhadap kemampuan listening siswa di SMAN 1 Singaraja, Bali. Penelitian ini merupakan penelitian eksperimen dengan menggunakan desain kuasi eksperimental, post-test only control group design. Melalui post-test, data akan dikumpulkan dimana nantinya hasil post-test dari kedua grup akan dianalisis. Hasil temuan menunjukkan bahwa skor rata-rata grup eksperimen lebih besar dari grup control, yaitu 80,03 > 75,49. Ini menunjukkan bahwa grup yang diberikan perlakuan dengan TED-Ed memiliki hasil yang lebih baik dari grup yang diberi media berbasis audio. Selain itu, nilai sig. (2-tailed) dari independent sample t-test dibawah 0,5, yaitu 0,003. Berarti, terdapat efek yang signifikan dari penggunaan TED-Ed terhadap kemampuan listening siswa. Oleh karenanya, dapat dikatakan bahwa TED-Ed mempengaruhi kemampuan listening siswa dan membuat performa siswa lebih baik dibanding dengan penggunaan media berbasis audio.